American wrestler [videorecording (DVD)] : the wizard - Ranarivelo, Alex; Fichtner, William; Voight, Jon, 1938-; Johnson, Lia Marie (Warner Bros. Home Entertainment, 2017)
When a teenage boy flees his homeland of Iran for America, he joins his school's wrestling team.